Project-Based Learning: A Hands-On Activity to Improve Students' Scientific Writing Skills through Lesson Study in Microtechnique Course - Permana, Tutut Indria; Wahyuni, Sri (FMIPA UNNES, 2019)
Project-based learning has been recognized as a dynamic classroom approach in which students actively explore real-world problems to obtain deeper knowledge. This study aimed to describe the implementation of project-based learning to improve students’ scientific writing skills. This action research study conducted based on Lesson Study (LS) which incorporated plan-do-see phase. The descriptive research was using 40 undergraduate students in the sixth semester in Biology Education Department, Faculty of Teacher Training and Education, Universitas Muhammadiyah Malang who attended Microtechnique course. The students’ scientific writing skills were measured using student worksheet which asked them to develop a scientific article. The measured parameters were how student proposed introduction, problem statement, method, result, discussion, conclusion, and reference. The data were analyzed descriptively. The result showed that students’ scientific writing skills were improved after implementing project-based learning. Some of the obstacles to implementing LS were related to the schedule and preparation. It can be resolved by conducting more intense coordination and regular discussions involving all research members.